2020
DOI: 10.1093/abbs/gmaa116
|View full text |Cite
|
Sign up to set email alerts
|

ARG1 functions as a tumor suppressor in breast cancer

Abstract: Arginase I (ARG1) is a cytosolic enzyme that catalyzes the hydrolysis of L-arginine to L-ornithine and urea. The association of ARG1 with cancer has mostly been focused on the ARG1 released by tumor-associated myeloid cells in tumor microenvironment. However, the role of ARG1 expressed in cancer cells is unclear. Here, we showed that the expression of ARG1 in human breast cancer (BC) is related to a good prognosis in BC patients. Overexpression of ARG1 suppresses BC cell proliferation and migration in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Inhibitors of this pathway are streaming into different phases of clinical trials, and some of them have successfully made their way to the market. [ 61 ] Arg1, a cytosolic enzyme that catalyzes the hydrolysis of L‐arginine (Arg) to L‐ornithine and urea, [ 63 ] has also been regarded as a characteristic feature or a trigger of T cell exhaustion. [ 62 ] Its high expression is associated with poor prognosis in different types of cancers, including melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of this pathway are streaming into different phases of clinical trials, and some of them have successfully made their way to the market. [ 61 ] Arg1, a cytosolic enzyme that catalyzes the hydrolysis of L‐arginine (Arg) to L‐ornithine and urea, [ 63 ] has also been regarded as a characteristic feature or a trigger of T cell exhaustion. [ 62 ] Its high expression is associated with poor prognosis in different types of cancers, including melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the level of Arg-1 decreases with high concentrations of L-norvaline, which functions as an Arg-1 inhibitor. Expression of Arg-1 leads to under-expression of p-AKT, resulting in deactivation of the AKT signaling pathway in BC cells; therefore, arg-1 acts as a tumor suppressor in BC [ 36 ]. The relationships between the abundance of Rothia genus, the level of norvaline, and the level of Arg-1 in breast tissue tumor requires further studies to understand the mechanism of the influence of Rothia and the metabolite norvaline on tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ARG1 is related to proliferation and migration in breast cancer and hepatocellular carcinoma (You et al, 2018;Ming et al, 2020). Therefore, we utilized western blotting and immunofluorescence to observe whether the proliferation or apoptosis of fetal lung cells was affected by Arg1 knockdown.…”
Section: Knockdown Of Arg1 In Fetal Lungs Induces Apoptosis Of Alveol...mentioning
confidence: 99%